Novel Techniques for Micro and Nanoplastics Analysis: A Review - Meehnian, Harmanpreet; Singh, Gurmeet; Rustagi, Sarvesh; Randhawa, Jatinder Singh (Asian Journal of Chemistry, 2025)
Microplastics contamination has received increased attention, due to its ubiquitous prevalence and possible hazards to the environment. It is critically necessary to have trustworthy techniques and tools for rapidly analyzing microplastics smaller than 5 mm. The analytical techniques for microplastics research such as sampling, identification and quantification are reviewed critically. Here both traditional and cutting-edge techniques for analyzing microplastics have been summarized. Furthermore, the present review focused on the current applications of microplastics analysis using, microscopy, Fourier transform infrared spectroscopy, scanning electron microscope, dynamic light scattering, thermal analysis, differential scanning calorimetry, pyrolysis-mass spectrometry and the highly advanced techniques includes automated image analysis, infrared hyperspectral imaging, microplastic sensors and electrochemical sensors.